2021
DOI: 10.3389/fpsyt.2021.621918
|View full text |Cite
|
Sign up to set email alerts
|

Relational Spirituality and Transgenerational Obligations: The Role of Family in Lay Explanatory Models of Post-traumatic Stress Disorder in Male Cameroonian Asylum Seekers and Undocumented Migrants in Europe

Abstract: Context: Diasporic Cameroonians are increasingly leading a transnational life in which family members are sustained through networks of relations and obligations. However, before arriving in Europe, the vast majority of African migrants who take the Mediterranean route are exposed to trauma and hardship. Moreover, the joint occurrence of forced displacement, trauma, and extended separation from families has a significant impact on mental health.Objectives: This study explores the role of culture-specific conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Faith has been shown to counter the adverse effects of adversity and trauma among African-origin populations [ 123 ] and to contribute to positive mental health outcomes [ 124 ]. Moreover, seeking comfort in religion has been found to be a major coping strategy for refugees from Sub-Saharan Africa [ 125 ] and intrinsic religiosity was associated with lower depression among caregivers of people living with HIV in Namibia [ 126 ]. Not surprisingly, religion is seen as a main pillar of African resilience and psychological health [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faith has been shown to counter the adverse effects of adversity and trauma among African-origin populations [ 123 ] and to contribute to positive mental health outcomes [ 124 ]. Moreover, seeking comfort in religion has been found to be a major coping strategy for refugees from Sub-Saharan Africa [ 125 ] and intrinsic religiosity was associated with lower depression among caregivers of people living with HIV in Namibia [ 126 ]. Not surprisingly, religion is seen as a main pillar of African resilience and psychological health [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migration interrupts relationships, social activities, social networks, informal relationships, and, therefore, cultural knowing. Growing up in a particular religious tradition within a particular community influences children with regards to the transmission of values and religious identity (Grupp et al 2021). This religious influence can range from positive to negative.…”
Section: Presence and Absence Of Relationshipsmentioning
confidence: 99%
“…However, past research on coping strategies among refugees and asylum-seekers from different Sub-Saharan African origins has reported that the most common coping strategies include faith and religion, social support, and various cognitive strategies [10,11]. An abundant body of research on African refugees and asylum-seeking migrants from different countries of origin has emphasized the role of spirituality and the commitment to a religion as an essential coping strategy in overcoming trauma and hardship [12][13][14]. In this regard, scholars have described belief systems in general, including religious, social, or political beliefs, as powerful shared strategies that allow individuals to better process traumatic experiences and to better cope with the symptoms of PTSD [15,16].…”
Section: Introductionmentioning
confidence: 99%